The Tapes Complex (Nico Pérez Terrane, Uruguay): Constraining the Mesoproterozoic evolution of the Río de la Plata Craton - Gaucher, Claudio (2021)
The Tapes Complex crops out in the southeastern Nico Pérez Terrane (NPT) of the Río de la Plata Craton and forms part of a NE-trending Mesoproterozoic belt together with the Calymmian (1.48–1.43 Ga) Parque UTE and Mina Verdún groups. The complex is characterized by interbedded/tectonically interleaved metasedimentary (mainly siliciclastic) and metaultramafic rocks, with subordinate intercalations of metabasites, carbonate and chert, all metamorphosed in the greenschist facies. The age of the Tapes Complex is constrained by: (i) a U–Pb SIMS age of 1360 ± 12 Ma for the youngest detrital zircon, (ii) the K–Ar age of 1253 ± 32 Ma for synkinematic muscovite of the Zapicán thrust, which affects the unit, and (iii) an Sm–Nd isochronic age of 1403 ± 150 Ma for ultramafic and mafic rocks. The intruding Tapes Chico Syenite yielded a much younger U–Pb SIMS age of 601 ± 5 Ma, associated with Brasiliano-Pan African tectonism, negative εHf values (mean = −31), δ18O zircon ratios ranging between 5.45 and 6.68‰ V-SMOW and inherited zircons dated at 1774-1756 Ma. The best preserved mafic and ultramafic samples yielded Nd model ages (TDM) between 1.55 and 1.68 Ga, close to the assumed crystallization age, and positive εNd(t). Nd model ages of metasedimentary rocks vary between 1.8 and 3.1 Ga, which is interpreted as reflecting two contrasting sources: Archean units of the NPT and Mesoproterozoic mafic and ultramafic rocks, including fragments of oceanic crust. Chondrite-normalized REE patterns of metasedimentary rocks are characterized by LREE enrichment and lack of an Eu anomaly, similar to REE patterns of co-occurring metabasalts. High MgO concentrations, high Cr/V and low Y/Ni and Th/Sc ratios imply the involvement of ultramafic rocks in the source area, which is also supported by whole-rock Pb isotope data. A geodynamic evolution is envisaged, from an extensional tectonic setting between 1.48–1.43 Ga (rift or retroarc basin) into a compressional, retroarc foreland basin at ca. 1.25–1.20 Ga, the latter being probably related to the Kibaran Orogeny in the Namaqua-Natal Belt. It is proposed that the corresponding arc granites and high-grade metamorphic rocks are likely to be found in one of the several terranes in the Namaqua sector of the belt. The Apiaí Terrane (Ribeira Belt, Brazil) shows a similar geological record and evolution as the NPT, and maybe a fragment of the latter displaced to the NW by the Ibaré Shear Zone. The Tapes Complex is a key unit for understanding the assembly of the Río de la Plata and Kalahari cratons, and their incorporation into the Rodinia supercontinent.